2014
DOI: 10.1186/1472-6955-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Factors that act as facilitators and barriers to nurse leaders’ participation in health policy development

Abstract: BackgroundHealth policies impact on nursing profession and health care. Nurses' involvement in health policy development ensures that health care is safe, of a high quality, accessible and affordable. Numerous factors influence nurse leaders' ability to be politically active in influencing health policy development. These factors can be facilitators or barriers to their participation. There is scant research evidence from Eastern African region that draws attention to this topic. This paper reports part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 40 publications
(47 reference statements)
1
96
0
2
Order By: Relevance
“…Low/middle-income countries face educational and cultural barriers that preclude nurses from communicating effectively. Such barriers include a lack of nurse involvement in patient management, inadequate communication training and hierarchy within the medical team discouraging expression of concern or opinions 12. Giving the CICU nurse a lead position and making her the liaison between the clinical team and this hospital’s leadership was pivotal in achieving empowerment at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Low/middle-income countries face educational and cultural barriers that preclude nurses from communicating effectively. Such barriers include a lack of nurse involvement in patient management, inadequate communication training and hierarchy within the medical team discouraging expression of concern or opinions 12. Giving the CICU nurse a lead position and making her the liaison between the clinical team and this hospital’s leadership was pivotal in achieving empowerment at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…). Moreover, Shariff () found that lack of knowledge, skills and support, lack of enabling structures, lack of available resources and lack of involvement were perceived as barriers to nurse leaders’ involvement in health policy development.…”
Section: Background and Significancementioning
confidence: 99%
“…). Other reported facilitators for enhancing nurse leaders’ participation in health policy development were being involved, being knowledgeable and skilled, being supported, the presence of enabling structures, availability of resources and positive image of nursing (Shariff ).…”
Section: Background and Significancementioning
confidence: 99%
See 2 more Smart Citations